(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
During research carried out on the insect pests in a factory of spices and aromatic herbs located in the Bologna province (Emilia Romagna, Northern Italy), insects collected in 1998-99 by light traps sited inside the building were identified. As well as other infestants, Attagenus fasciatus (Thunberg) and Reesa vespulae (Milliron) were found. These two dermestids had never previously been recorded in Italy, either on stored products or outdoors. Both species are well-known pests found in buildings, on stored food products and other goods, so they are becoming widespread. A. fasciatus is widely distributed throughout the warmer regions of the world and was accidentally introduced, or is periodically re-imported, into various temperate countries by international trade. R. vespulae is a Nearctic species which has spread to several European and Asiatic countries for the same reason. Morphological notes useful for the identification of these dermestids and information about their biology and most frequently infested substrates are reported. In addition, a table listing the other main insects collected by light traps in the above spice factory is provided.